(untitled) - Brinkley, Captain F. (Boston, 1902)
This book introduce about refinements and pastimes of the miltary epoch. The early Tokugawa times. Middle period of the Tokugawa. Later period of the Tokugawa. The fall of the Tokugawa.
Keywords: Nhật Bản,Japan; Lịch sử,History